Современное пространство отношений искусства и потребителя - Шульга, Р. (Социология: теория, методы, маркетинг, 2005)
The publication reviews the problems emerging in the process of research of the art impact potential in modern conditions of its existence. Sociological analysis of the art influence on personality should take into account all the spectrum of factors and conditions, determining the character of modern consumption of art products.